The Geomagnetic Field Is a Contributing Factor for an Efficient Iron Uptake in Arabidopsis thaliana - Islam, Monirul; Maffei, Massimo E.; Vigani, Gianpiero (Frontiers in Plant Science, 2020)
The Earth’s magnetic field, defined as the geomagnetic field (GMF), is an unavoidable environmental factor for all living organisms. Variation in the GMF intensity was found to affect the content of some nutrients and their associated channels and transporters in Arabidopsis thaliana. In this work, we observed that reduction of the GMF to near null magnetic field (NNMF) affects the accumulation of the metal in plant tissues, mainly iron (Fe) and zinc (Zn) content, while the content of others metals such as copper (Cu) and manganese (Mn) is not affected. Accordingly, Fe uptake genes were induced in the roots of NNMF-exposed plants and the root Fe reductase activity was affected by transferring GMF-exposed plant to NNMF condition. Under Fe deficiency, NNMF-exposed plants displayed a limitation in the activation of Fe-deficiency induced genes. Such an effect was associated with the strong accumulation of Zn and Cu observed under NNMF conditions. Overall, our results provide evidence on the important role of the GMF on the iron uptake efficiency of plants.